2020
DOI: 10.1177/0022242920902722
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting Effort Versus Talent in Service Employee Performance: Customer Attributions and Responses

Abstract: Firms often attribute their service employees’ competent performance to either dedicated effort or natural talent. However, it is unclear how such practices affect customer evaluations of service employees and customer outcomes. Moreover, prior work has primarily examined attributions of one’s own performance, providing little insight on the impact of attributions of others’ performance. Drawing on research regarding the warmth–competence framework and performance attributions, the current research proposes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 59 publications
(107 reference statements)
2
47
0
Order By: Relevance
“… 2 Study 3a included many questions that assessed multiple constructs, so we followed Leung, Kim, and Tse ( 2020 ) and conducted confirmatory factor analysis to determine whether the constructs were distinct. Results showed that all items loaded on the intended factor, and the average variance extracted (AVE) exceeded .50 (psychological closeness = .64, perceived vulnerability = .59, arousal = .65, vividness/concreteness = .56, perceived control = .66).…”
mentioning
confidence: 99%
“… 2 Study 3a included many questions that assessed multiple constructs, so we followed Leung, Kim, and Tse ( 2020 ) and conducted confirmatory factor analysis to determine whether the constructs were distinct. Results showed that all items loaded on the intended factor, and the average variance extracted (AVE) exceeded .50 (psychological closeness = .64, perceived vulnerability = .59, arousal = .65, vividness/concreteness = .56, perceived control = .66).…”
mentioning
confidence: 99%
“…, 2021a). In addition, consumers perceive employees as warmer when attributing their service performance to perseverance rather than talent (Leung et al. , 2020).…”
Section: The Application Of the Scm In Marketingmentioning
confidence: 99%
“…Framing a company's competence as caused by employees' effort leads to better brand outcomes (word of mouth; idea provision behavior) than attributing brand competence to employees' talent (Leung et al, 2020). Framing competence as effort (vs. talent) led to higher perceived warmth, which mediated the effect of competence framing on brand outcomes.…”
Section: Service Marketingmentioning
confidence: 99%
“…However, two alternative interpretations were also mentioned in the review. One is that brand perception is social because consumers think about the people behind the brand such as the CEO (Centeno et al, 2019; Zeitoun et al, 2020) or employees (Leung et al, 2020; Zeitoun et al, 2020). The second is that consumers used their stereotypes about typical brand consumers to apply it to the brand (Aagerup, 2020; Antonetti & Maklan, 2016).…”
Section: Potential For Future Brands As Intentional Agents Framework Researchmentioning
confidence: 99%